Ethnography and evaluation: temporalities of complex systems and methodological complexity. Issue 1 (2nd January 2019) - Reynolds, Joanna; Lewis, Sue
Abstract: In public health there is increased focus on evaluating 'complex' interventions for health improvement, examining how their multiple components interact dynamically with the contextual system in which they are delivered. Amid this complexity framing are calls for methodologies that can facilitate contextual understanding as part of the evaluation process, including ethnography. However, while ethnography's attention to 'context' has been recognised as valuable for evaluation, few questions have been raised about the possible tensions of aligning what are quite different expectations for knowledge making in evaluation and in ethnography. This paper introduces a special section illustrating empirical examples of conducting ethnography for and with evaluation of 'complex' health interventions. Central to these experiences, this paper argues, are the concepts of time and temporality through which experience, change and knowledge making are invariably structured. It considers the different expectations for time and temporality in ethnographic and evaluation research, and how the 'long conversation' of ethnography aids interpretation of an intervention's interaction with the pasts, presents and possible futures of people's health experiences. Furthermore, in understanding time not as linear and constant but experienced through a series of encounters, ethnography highlights the spaces in between action and change, vital for understanding the complex dynamics of a health intervention in context. Through temporality, this paper and the related empirical papers present an intricate exploration of the challenges and productive opportunities posed by the use of ethnography for and with evaluation.